Environmentally friendly urea-formaldehyde resin glue and preparation method thereof
By adding modified additives and modified polyvinyl alcohol to the urea formaldehyde resin glue, the problems of poor water resistance and formaldehyde release of existing urea formaldehyde resin glue are solved, and an environmentally friendly urea formaldehyde resin glue with low formaldehyde release and excellent glue strength and water resistance are achieved.
Patent Information
- Application Number
- CN202410770072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing urea-formaldehyde resin glue has poor water resistance, which leads to the release of formaldehyde during long-term use of artificial board products, causing indoor pollution, and reducing the molar ratio of formaldehyde to urea will lead to poor resin bonding strength and water resistance.
By adding modified additives and modified polyvinyl alcohol, the free formaldehyde content in the prepared urea-formaldehyde resin glue is reduced. The modified additives enhance the photocatalytic performance by loading nanotitanium dioxide. The modified polyvinyl alcohol improves the curing speed and water resistance of the resin by grafting sodium methyl silicate.
It has achieved a low formaldehyde emission of environmentally friendly urea-formaldehyde resin glue, which has excellent glue strength and water resistance to meet environmental protection and performance needs.
Smart Images

Figure BDA0004893836680000071 
Figure BDA0004893836680000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to an environmentally friendly urea-formaldehyde resin adhesive and a preparation method thereof. Background Art
[0002] Urea-formaldehyde resin is synthesized by addition-condensation reaction of urea and formaldehyde in the presence of a catalyst. Generally, the "base-acid-base" synthesis process is adopted. The addition reaction occurs under alkaline conditions, and the condensation reaction occurs under acidic conditions. The initial urea-formaldehyde resin is formed by chemical combination, and then the insoluble final thermosetting resin is formed under the action of a curing agent or an auxiliary agent. Urea-formaldehyde resin is currently the most widely produced and applied adhesive for artificial boards because of its advantages such as simple production process, low cost, and abundant raw material sources. However, urea-formaldehyde resin has poor water resistance, and the prepared artificial board products will release formaldehyde for a long time, causing an increase in indoor pollution and seriously endangering human health. Existing urea-formaldehyde resins are cross-linked and cured at high temperatures. The hydroxyl groups on the urea-formaldehyde resin can form hydrogen bonds with the hydroxyl groups on the surface of the wood to achieve the effect of bonding the wood boards. However, their water resistance is poor. The reason is that after the glue layer is immersed in water, the water molecules will continue to destroy the hydrogen bonds formed between the glue layer and the wood boards. When the force of the hydrogen bonds is not enough to support the bonding between the wood boards, the plywood will crack. In addition, in order to improve the environmental protection level of artificial board products, manufacturers generally produce urea-formaldehyde resins by reducing the molar ratio of formaldehyde to urea to reduce the formaldehyde pollution generated by the adhesive products. However, reducing the molar ratio will significantly lead to a decrease in the content of branched structural units N, N-dimethylol and branched methylene bridge bonds in the resin prepolymer, and the resin molecules are difficult to solidify to form a dense cross-linked structure, which ultimately leads to poor resin bonding strength and water resistance. Summary of the invention
[0003] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide an environmentally friendly urea-formaldehyde resin glue and a preparation method thereof. By adding modified additives and modified polyvinyl alcohol, the free formaldehyde content in the prepared urea-formaldehyde resin glue is reduced, the prepared plywood has low formaldehyde release, is safe and environmentally friendly, and has excellent bonding strength and water resistance.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 45-60 parts of urea, 50-80 parts of formaldehyde solution, 10-25 parts of modified additives, and 5-15 parts of modified polyvinyl alcohol;
[0006] The modified additive is prepared by grafting isophorone diisocyanate onto multi-walled carbon nanotubes loaded with nano-titanium dioxide and further sealing the isocyanate groups with sodium bisulfite; the modified polyvinyl alcohol is modified polyvinyl alcohol grafted with sodium methyl silicate.
[0007] Preferably, the preparation method of the modified additive comprises the following steps:
[0008] A. Add multi-walled carbon nanotubes to a concentrated nitric acid solution with a concentration of 60-75%, and then place it under reflux reaction at 105-120° C. for 10-12 hours. After the reaction is completed, filter, wash, and dry to prepare purified multi-walled carbon nanotubes;
[0009] B. Tetrabutyl titanate and anhydrous ethanol were mixed and stirred for 15 to 30 minutes, and then acetic acid and purified multi-walled carbon nanotubes were added and stirred for 10 to 12 hours. The obtained gel was placed in an oven for drying, and then placed in a muffle furnace with a heating rate of 5 to 10°C / min and calcined at 450 to 500°C for 4 to 6 hours to prepare a titanium dioxide-carbon nanotube composite material;
[0010] C. Ultrasonic dispersion of titanium dioxide-carbon nanotube composite material in N,N-dimethylformamide, then adding isophorone diisocyanate and dibutyltin dilaurate, raising the temperature to 70-85°C, stirring and reacting in a nitrogen atmosphere for 6-8 hours, filtering after the reaction is completed, ultrasonically dispersing the obtained filter cake in N,N-dimethylformamide, then adding it to a mixed solution of sodium bisulfite aqueous solution and ethanol, and reacting at 20-25°C for 5-7 hours. After the reaction is completed, filtering, washing and drying are performed to prepare a modified additive.
[0011] Preferably, in step B, the addition ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid and purified multi-walled carbon nanotubes is 20-25 mL: 180-200 mL: 13-18 mL: 6-8 g.
[0012] Preferably, in step C, the mass ratio of the titanium dioxide-carbon nanotube composite material to isophorone diisocyanate is 1:7-12.
[0013] Preferably, the mass concentration of the sodium bisulfite aqueous solution in step C is 30-45%.
[0014] Preferably, the preparation method of the modified polyvinyl alcohol is as follows: polyvinyl alcohol is added to deionized water at 80-90° C. to prepare a polyvinyl alcohol aqueous solution, and then sodium methyl silicate is added, and the mixture is reacted at 80-85° C. for 2-3 hours to prepare the modified polyvinyl alcohol.
[0015] Preferably, the mass ratio of the polyvinyl alcohol aqueous solution to sodium methyl silicate is 8-12:1; and the mass concentration of the polyvinyl alcohol aqueous solution is 15-20%.
[0016] Preferably, the method for preparing the environmentally friendly urea-formaldehyde resin adhesive as described above comprises the following steps:
[0017] S1. Add formaldehyde solution to the reactor, adjust the pH of the system to 7.7-8.4 with sodium hydroxide solution, then place the reactor in a water bath, heat it to 40-45°C and keep it warm for 10-15 minutes, add the first portion of urea and modified polyvinyl alcohol, heat it to 85-92°C and react for 40-60 minutes;
[0018] S2, adding formic acid solution to adjust the system pH to 4-5.5, maintaining the reaction temperature at 85-92°C, and using a rubber-tipped dropper to absorb the reaction solution and drip into clean water during the reaction, measuring the degree of reaction, and when the reaction solution appears white mist in the water, lowering the reaction temperature to 75-82°C;
[0019] S3, using sodium hydroxide solution to adjust the system pH to 6-7, adding the second portion of urea to react for 20-40 minutes;
[0020] S4, using sodium hydroxide solution to adjust the pH value of the system to 8-8.5, adding the third portion of urea and the modified additive to react for 0.5-1h, and after the reaction is completed, cooling to room temperature and discharging the material to prepare the environmentally friendly urea-formaldehyde resin glue.
[0021] Preferably, the mass concentration of the formaldehyde solution is 30-40%; the mass concentration of the sodium hydroxide solution is 20-30%; and the mass concentration of the formic acid solution is 25-50%.
[0022] Preferably, the mass ratio of the first portion of urea, the second portion of urea and the third portion of urea is 4:5:1.
[0023] Beneficial effects of the present invention:
[0024] The invention uses concentrated nitric acid to purify multi-walled carbon nanotubes, so that the surface of the purified multi-walled carbon nanotubes is rich in hydroxyl groups, and then nano-titanium dioxide is loaded on the surface of the purified multi-walled carbon nanotubes by a sol-gel method to prepare a titanium dioxide-carbon nanotube composite material, wherein the nano-titanium dioxide has a photocatalytic property and can catalytically degrade toxic gases in the air under ultraviolet or visible light irradiation, decompose the reducing free formaldehyde in the resin, and the ultraviolet light has a higher formaldehyde reduction efficiency, but the light response region of the nano-titanium dioxide photocatalyst is mainly concentrated in the ultraviolet light region, and the utilization rate of visible light is low. By loading nano-titanium dioxide on the surface of multi-walled carbon nanotubes, the light response range can be expanded and the photocatalytic activity can be increased. The multi-walled carbon nanotubes have a well-developed surface pore structure, which provides a channel for the release of formaldehyde. At the same time, they have excellent adsorption properties. When loaded with nano-titanium dioxide, formaldehyde molecules can be adsorbed on the catalyst surface, increasing the contact area between nano-titanium dioxide and formaldehyde, thereby enhancing the photocatalytic performance. At the same time, multi-walled carbon nanotubes have good electrical conductivity. The use of loaded nano-titanium dioxide can effectively improve the separation efficiency of photogenerated electrons and holes, making the nano-titanium dioxide photocatalyst have higher catalytic activity.
[0025] In addition, the present invention utilizes the highly reactive isocyanate groups directly connected to the cyclohexane ring in isophorone diisocyanate to react with the hydroxyl groups on the surface of the titanium dioxide-carbon nanotube composite material, so that the isocyanate groups are grafted onto the surface of the titanium dioxide-carbon nanotube composite material, and further performs a sealing treatment on the titanium dioxide-carbon nanotube composite material with sodium bisulfite, thereby grafting -NHCOSO3Na groups on the surface of the titanium dioxide-carbon nanotube composite material to prepare a modified additive that can be uniformly dispersed in a matrix. The -NHCOSO3Na groups on the surface of the modified additive can be automatically unblocked at high temperatures to form -NCO, which can react chemically with the -NH2 or -COOH groups in the matrix to form a three-dimensional cross-linked network structure, significantly improving the interface bonding force between the titanium dioxide-carbon nanotube composite material and the matrix, while preventing water molecules from entering, thereby improving the water resistance of the material. In addition, the isocyanate groups on the isophorone diisocyanate react with the hydroxyl groups on the titanium dioxide-carbon nanotube composite material or the resin to generate non-hydrophilic and highly stable carbamates, and the isocyanate groups can be combined with the hydroxyl groups on the wood board, thereby improving the water resistance of the material. The present invention utilizes sodium methyl silicate to graft polyvinyl alcohol. The introduction of silanol groups helps to cure faster. Sodium methyl silicate can improve the flexibility and hydrophobicity of the substrate, and has the advantages of low cost, environmental protection and no pollution. Polyvinyl alcohol is grafted with sodium methyl silicate to undergo a cross-linking reaction to obtain modified polyvinyl alcohol containing Si-OC functional groups, thereby improving the water resistance of the substrate. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1 A method for preparing the modified additive comprises the following steps:
[0028] A. Take 10g of multi-walled carbon nanotubes and add them to a concentrated nitric acid solution with a concentration of 70%, then place it under reflux reaction at 115°C for 12h. After the reaction is completed, filter, wash and dry to prepare purified multi-walled carbon nanotubes;
[0029] B. 24 mL of tetrabutyl titanate and 200 mL of anhydrous ethanol were mixed and stirred for 20 min, and then 17 mL of acetic acid and 8 g of purified multi-walled carbon nanotubes were added and stirred for 12 h. The obtained gel was placed in an oven to dry, and then placed in a muffle furnace with a heating rate of 5 ° C / min and calcined at 500 ° C for 4 h to prepare a titanium dioxide-carbon nanotube composite material;
[0030] C. Take 3g of titanium dioxide-carbon nanotube composite material and ultrasonically disperse it in 150mL of N,N-dimethylformamide, then add 30g of isophorone diisocyanate and 0.002g of dibutyltin dilaurate, raise the temperature to 80°C, stir and react for 8h in a nitrogen atmosphere, filter after the reaction is completed, ultrasonically disperse the obtained filter cake in 60mL of N,N-dimethylformamide, then add it to a mixed solution of 100mL of 40% sodium bisulfite aqueous solution and 25mL of ethanol, place it at 20°C to react for 7h, filter after the reaction is completed, wash and dry to prepare a modified additive.
[0031] Embodiment 2 A method for preparing modified polyvinyl alcohol is specifically as follows:
[0032] Polyvinyl alcohol was added to 85° C. deionized water to prepare a 20% polyvinyl alcohol aqueous solution, and then 50 g of the polyvinyl alcohol aqueous solution was added with 5 g of sodium methyl silicate, and the mixture was reacted at 80-85° C. for 2-3 hours to prepare modified polyvinyl alcohol.
[0033] Example 3 An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 45 parts of urea, 50 parts of formaldehyde solution, 12 parts of modified additives, and 5 parts of modified polyvinyl alcohol.
[0034] The method for preparing the environmentally friendly urea-formaldehyde resin adhesive comprises the following steps:
[0035] S1. Add 37% formaldehyde solution to the reactor, adjust the pH of the system to 8 with 30% sodium hydroxide solution, then place the reactor in a water bath, heat it to 45°C and keep it warm for 15 minutes, add the first portion of urea and modified polyvinyl alcohol, heat it to 92°C and react for 40 minutes;
[0036] S2. Add 50% formic acid solution to adjust the pH of the system to 5, maintain the reaction temperature at 92°C, and use a rubber-tipped dropper to absorb the reaction solution and drip into clean water during the reaction, measure the reaction degree, and when the reaction solution appears white mist in the water, reduce the reaction temperature to 82°C;
[0037] S3, using 30% sodium hydroxide solution to adjust the system pH to 6.5, adding the second portion of urea to react for 30 minutes;
[0038] S4. Use 30% sodium hydroxide solution to adjust the pH value of the system to 8, add the third portion of urea and the modified additive to react for 1 hour, and after the reaction is completed, cool to room temperature and discharge the material to prepare the environmentally friendly urea-formaldehyde resin glue.
[0039] The mass ratio of the first portion of urea, the second portion of urea and the third portion of urea is 4:5:1.
[0040] Example 4 An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 55 parts of urea, 67 parts of formaldehyde solution, 20 parts of modified additives, and 10 parts of modified polyvinyl alcohol.
[0041] The preparation method of the above-mentioned environmentally friendly urea-formaldehyde resin adhesive is the same as that in Example 3.
[0042] Example 5 An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 60 parts of urea, 73 parts of formaldehyde solution, 25 parts of modified additives, and 14 parts of modified polyvinyl alcohol.
[0043] The preparation method of the above-mentioned environmentally friendly urea-formaldehyde resin adhesive is the same as that in Example 3.
[0044] Comparative Example 1 An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 60 parts of urea, 73 parts of formaldehyde solution, 25 parts of nano-titanium dioxide, and 14 parts of modified polyvinyl alcohol.
[0045] The preparation method of the above-mentioned environmentally friendly urea-formaldehyde resin adhesive is the same as that in Example 3.
[0046] Comparative Example 2: An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 60 parts of urea, 73 parts of formaldehyde solution, 25 parts of titanium dioxide-carbon nanotube composite material, and 14 parts of modified polyvinyl alcohol.
[0047] The preparation method of the above-mentioned environmentally friendly urea-formaldehyde resin adhesive is the same as that in Example 3.
[0048] Comparative Example 3: An environmentally friendly urea-formaldehyde resin adhesive comprises the following components in parts by weight: 60 parts of urea, 73 parts of formaldehyde solution, 25 parts of a modified additive, and 14 parts of polyvinyl alcohol.
[0049] The preparation method of the above-mentioned environmentally friendly urea-formaldehyde resin adhesive is the same as that in Example 3.
[0050] Performance Testing
[0051] The urea-formaldehyde resin glue prepared in Examples 3-5 and Comparative Examples 1-3 was subjected to performance testing:
[0052] a. Physical and chemical properties test: The solid content, free formaldehyde content, curing time and viscosity were determined in accordance with GB / T14074.7-2006. The data results are shown in Table 1.
[0053] Table 1 Test results of physical and chemical properties of samples
[0054]
[0055] It can be seen from the data in Table 1 that the urea-formaldehyde resin glue prepared in the embodiment of the present invention has a low free formaldehyde content, and the addition of the modified additive can effectively reduce the free formaldehyde content of the urea-formaldehyde resin glue, thereby meeting environmental protection requirements.
[0056] b. Preparation of plywood: Three-layer veneer with a single-sided glue coating of 200g / m 2 ; Pre-pressing process: unit pressure 0.7MPa, time 1h; hot pressing process: unit pressure 0.7MPa, temperature 125℃, time 100s / mm. Three plywoods were prepared for each factor level.
[0057] (1) Bonding strength test: The bonding strength of Class II plywood in GB / T 17657-2013 was measured. Each group was measured three times in parallel. The arithmetic mean of the results was taken. The data results are shown in Table 2.
[0058] (2) Formaldehyde emission test: Referring to GB / T 17657-2013, the perforation extraction method was used for determination. The data results are shown in Table 2.
[0059] (3) Water resistance test: Referring to GB / T 17657-2013, the water absorption thickness expansion rate was measured after 24 hours, and the data results are shown in Table 2.
[0060] Table 2 Test results of sample performance
[0061]
[0062] It can be seen from the data in Table 2 that the plywood prepared in Examples 3-5 of the present invention has low formaldehyde emission, high bonding strength and excellent water resistance. Among them, the modified additive in Comparative Example 1 is nano titanium dioxide, and the measured formaldehyde emission is significantly higher than that in Examples 3-5, and the bonding strength and water resistance are slightly worse than those in Examples 3-5. The modified additive in Comparative Example 2 is titanium dioxide-carbon nanotube composite material, and the measured bonding strength and water resistance are slightly worse than those in Examples 3-5. In Comparative Example 3, polyvinyl alcohol is not modified, and the measured water absorption thickness expansion rate is significantly higher than that in Examples 3-5, and the water resistance is reduced.
[0063] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0064] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. An environmentally friendly urea-formaldehyde resin adhesive, characterized in that: The invention comprises the following components in parts by weight: 45-60 parts of urea, 50-80 parts of formaldehyde solution, 10-25 parts of modified additives, and 5-15 parts of modified polyvinyl alcohol; The modified additive is prepared by loading nano-titanium dioxide onto multi-walled carbon nanotubes, grafting isophorone diisocyanate, and further sealing the isocyanate groups with sodium bisulfite; The modified polyvinyl alcohol is polyvinyl alcohol grafted with sodium methyl silicate; The preparation method of the modified additive comprises the following steps: A. Add multi-walled carbon nanotubes to a concentrated nitric acid solution with a concentration of 60-75%, and then place it under reflux at 105-120° C. for 10-12 hours. After the reaction is completed, filter, wash, and dry to prepare purified multi-walled carbon nanotubes; B. Take tetrabutyl titanate and anhydrous ethanol and mix them for 15-30 minutes, then add acetic acid and purified multi-walled carbon nanotubes and stir for 10-12 hours, dry the obtained gel in an oven, and then calcine it at 450-500° C. for 4-6 hours in a muffle furnace with a heating rate of 5-10° C. / min to prepare a titanium dioxide-carbon nanotube composite material; C. Ultrasonic dispersion of titanium dioxide-carbon nanotube composite material in N, N-dimethylformamide, then adding isophorone diisocyanate and dibutyltin dilaurate, heating to 70-85° C., stirring and reacting for 6-8 hours in a nitrogen atmosphere, filtering after the reaction is completed, ultrasonically dispersing the obtained filter cake in N, N-dimethylformamide, then adding it to a mixed solution of sodium bisulfite aqueous solution and ethanol, placing it at 20-25° C. for reaction for 5-7 hours, filtering after the reaction is completed, washing, and drying to prepare a modified additive; The preparation method of the modified polyvinyl alcohol is specifically as follows: polyvinyl alcohol is added to deionized water at 80-90° C. to prepare a polyvinyl alcohol aqueous solution, and then sodium methyl silicate is added, and the solution is reacted at 80-85° C. for 2-3 hours to prepare the modified polyvinyl alcohol.
2. The environmentally friendly urea-formaldehyde resin adhesive according to claim 1, characterized in that: In the step B, the addition ratio of tetrabutyl titanate, anhydrous ethanol, acetic acid and purified multi-walled carbon nanotubes is 20-25 mL: 180-200 mL: 13-18 mL: 6-8 g.
3. The environmentally friendly urea-formaldehyde resin adhesive according to claim 1, characterized in that: In the step C, the mass ratio of the titanium dioxide-carbon nanotube composite material to isophorone diisocyanate is 1:7-12.
4. The environmentally friendly urea-formaldehyde resin adhesive according to claim 1, characterized in that: The mass concentration of the sodium bisulfite aqueous solution in step C is 30-45%.
5. The environmentally friendly urea-formaldehyde resin adhesive according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol aqueous solution to sodium methyl silicate is 8-12:1; the mass concentration of the polyvinyl alcohol aqueous solution is 15-20%.
6. The method for preparing the environmentally friendly urea-formaldehyde resin adhesive according to claim 1, characterized in that: The following steps are involved: S1. Add formaldehyde solution to the reactor, adjust the pH of the system to 7.7-8.4 with sodium hydroxide solution, then place the reactor in a water bath, heat it to 40-45°C and keep it warm for 10-15 minutes, add the first portion of urea and modified polyvinyl alcohol, heat it to 85-92°C and react for 40-60 minutes; S2. Add formic acid solution to adjust the pH of the system to 4-5.5, maintain the reaction temperature at 85-92°C, and use a rubber-tipped dropper to absorb the reaction solution and drip into clean water during the reaction, measure the reaction degree, and when the reaction solution appears white mist in the water, reduce the reaction temperature to 75-82°C; S3, using sodium hydroxide solution to adjust the system pH to 6-7, adding the second portion of urea to react for 20-40 minutes; S4. Use sodium hydroxide solution to adjust the pH value of the system to 8-8.5, add the third portion of urea and the modified additive to react for 0.5-1h, and after the reaction is completed, cool to room temperature and discharge the material to prepare the environmentally friendly urea-formaldehyde resin glue.
7. The method for preparing the environmentally friendly urea-formaldehyde resin adhesive according to claim 6, characterized in that: The mass concentration of the formaldehyde solution is 30-40%; the mass concentration of the sodium hydroxide solution is 20-30%; and the mass concentration of the formic acid solution is 25-50%.
8. The method for preparing the environmentally friendly urea-formaldehyde resin adhesive according to claim 6, characterized in that: The mass ratio of the first portion of urea, the second portion of urea and the third portion of urea is 4:5:1.
Citation Information
Patent Citations
Preparation method of carbon nano tube modified urea resin adhesive
CN103275660A
Cited By
ENF-grade melamine modified urea-formaldehyde glue powder as well as preparation method and application thereof
CN121759125A
An enf-grade melamine-modified urea-formaldehyde adhesive powder, a preparation method and application thereof
CN121759125B